(untitled) (Research, Society and Development, 2024)
This research aimed to evaluate whether there was a difference in the results of the analysis of coffee leaves packed in paper and plastic packaging (with and without holes). We also sought to verify whether the time in which foliar analysis was performed (eighth day and fifteenth day after collection) followed the same trend observed for the samples that were collected and immediately analyzed. To achieve the proposed objective, the leaves of the plants were initially collected on a farm located in the Boa Esperança region and then taken to the laboratory for analysis. The results were evaluated using unsupervised Pattern Recognition composed of Hierarchical Cluster Analysis (HCA) and Principal Component Analysis (PCA). It was found that regardless of the type of packaging in which the coffee leaves were packed, there is a high similarity between the samples analyzed on the day of collection and on the eighth day after collection, which, in turn, are different from those evaluated on the tenth. fifth day after collection. Such results allow us to infer that the influence of time after collection overlaps with the influence of the type of packaging. Therefore, it can be concluded that coffee leaves can be analyzed up to the eighth day after being collected, being packaged in any type of packaging studied (paper, plastic with holes and plastic without holes).